HUBUNGAN KARAKTER WIRAUSAHA DAN PENGETAHUAN KEWIRAUSAHAAN DENGAN PERILAKU BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN AKUNTANSI UNS - Wafiq Abrar Wasdiyansyach; Lies Nurhaini (Universitas Sebelas Maret, 2025)
This study aims to examine the relationship between entrepreneurial character and entrepreneurial knowledge with entrepreneurial behavior. This research employed a descriptive quantitative method. The sample was selected using random sampling, consisting of 108 students. The data collection technique used in this study was a questionnaire. The data analysis techniques included descriptive statistical analy sis, prerequisite tests of analysis, and hypothesis testing. The results of this study indicate that: (1) there is a positive and significant relationship between entrepreneurial character and entrepreneurial behavior among Accounting Education students of Sebelas Maret University. This is indicated by the result of tcount > ttable (9.574 > 1.65909), with a significance value of 0.001 < 0.05; (2) there is a positive and significant relationship between entrepreneurial knowledge and entrepreneurial behavior among Account ing Education students of Sebelas Maret University. This is indicated by the result of tcount > ttable (2.713 > 1.65909), with a significance value of 0.008 < 0.05; (3) there is a positive and significant rela tionship between entrepreneurial character and entrepreneurial knowledge with entrepreneurial behavior among Accounting Education students of Sebelas Maret University. This is indicated by the result of Fcount > Ftable (244.191 > 3.080), with a significance value of 0.001 < 0.05.Keywords: Entrepreneurial Behavior; Entrepreneurial Character; Entrepreneurial Knowledge